La souffrance au travail des soignants : une analyse des conséquences délétères des outils de gestion - Fatéma Safy-Godineau (La Nouvelle Revue du Travail)
The evolution of hospital reforms leads to a denaturation of the function of health facilities that become firms deemed on the production of their care activity and economic performance obtained by these activities. By this denaturation, health facilities become a receptacle of injunctions where caregivers are faced with paradoxes often difficult to resolve: economic performance vs. quality, regulative and normative framework vs. customization of care, professional division vs. continuity of care, organizational values vs. professional values. Furthermore, it generates a process of disqualification of trades of care because it is increasingly asked caregivers to become technicians, ‘effective’ people, in regard to management costs of their care activity and no longer of work on human being. What then is the impact of mutations caused by the hospital reforms on work health of caregivers? More specifically, what is the link between managerial support mode of these transformations and the alteration of work heath on caregivers?To answer these questions, we rely on the concept of suffering to work with for key reading the conservation of resources theory. Our research is positioned in the comprehensive paradigm and the methodology used is qualitative. The field of study chosen for our investigation is a medico-social establishment, semi-public nature, and our research sample consists of 28 caregivers (nurses and nursing aide). The research results show that hospital reforms deplete the organizational resources, that help individuals in their effort at work and in achieving the objectives of the work, as the subjective resources enabling the individual to define himself, impacting thus the health of caregivers to the extent where the injury to health at work has its origins in the potential or actual loss of subjective resources. Results also argue that the suffering at work result from a deficit within the role of proximity supervisor, because managers tools and logics which get into health facilities lead directions and proximity managers towards remote concerns from the daily difficulties of the care activity and the necessary local regulation that they need.